O conceito de gestão na arquivologia e administração: uma análise da produção científica - LOBATO JUNIOR, Luiz Carlos Maia (2017)
The present work brings the Archiving and the Administration for an analysis of the contexts in which they involve both these disciplines as well as their characteristics. The objectives of the study were to map the "Management" theme within the two disciplines, analyzing the subtopics related to them, the concept of "Management" in both disciplines and discussing the subtopics recovered as well as the articles retrieved with the intention of identifying possible relations Interdisciplinary. It was found that although the theme is common for Archives and Management, other areas of knowledge also use the main theme through the sub-themes. Some interdisciplinary relations between the two fields of knowledge were also perceived. It concludes by saying that it is an initial study, and it can be developed by future researchers who are interested in this subject of Archives and Administration.